Two dimensional porous 3d-4f heterometallic coordination polymers constructed by pyridine-2,3-dicarboxylic acid - Yang, Ting-Hai
Reactions of pyridine-2,3-dicarboxylic acid (pydcH(2)), cobalt acetate and lanthanide nitrate under hydrothermal conditions result in four new 3d-4f heterometallic coordination polymers, namely,[LnCo(pydc)(3)(H2O)(3)]center dot 9H(2)O {Ln = Dy (1), Ho (2), Er (3) and Tm (4)}. All compounds were characterized by elemental analysis, IR spectroscopy, SEM, EDS, thermal gravimetric analysis and X-ray diffraction. The compounds feature a two dimensional (2-D) layer structure with large apertures, in which each pydc2-ligand links two metal centers and each metal center is bonded to three pydc(2-) and vice versa. The adsorption and catalytic properties of compound 1 were investigated.